Perfeksionisme dan Stres Mengerjakan Skripsi - Sesilia Dewi Saraswati; Timotius Raditya Hernawa (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2022)
Abstract. This study aims to determine the relationship between perfectionism and stress of completing a thesis on students. The participants in this study were 179 undergraduate students completing a thesis. The hypotheses proposed that 1) there is a positive relationship between Self-Oriented Perfectionism (SOP) and stress of completing a thesis, 2) there is a positive relationship between Other-oriented Perfectionism (OOP) and stress of completing a thesis, 3) there is a positive relationship between Socially-prescribed Perfectionism (SPP) and stress of completing a thesis, and 4) there is a relationship between perfectionism and stress of completing a thesis. This study used quantitative methods. The data were collected using Skala Stress Mengerjakan Skripsi (α = 0,926) and a scale modified from Hewitt and Flett (1991)’s Multidimensional Perfectionism Scale (αstrat= 0.888).  This study used nonparametric analysis Spearman's Rho to analyze hypothesis 1), and parametric analysis Pearson's Product Moment to analyze hypothesis 2), 3), 4). The results showed that 1) there was no relationship between self-oriented perfectionism (SOP) and  stress of completing a thesis (rs = 0.094; p = 0.106 0.05), 2) there was a positive relationship between other-oriented perfectionism (OOP) and  stress of completing a thesis (r = 0.247; p = 0.000 0.05), 3) there was positive relationship between socially-prescribed perfectionism (SPP) and stress of completing a thesis (r = 0.408; p = 0.000 0.05), and 4) there was the relationship between perfectionism and the stress of completing a thesis (r = 0.329; p = 0.000). Keywords: perfectionism, stress, academic stress, stress of completing a thesis, students